2013
DOI: 10.1016/j.jviromet.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of current rapid HIV test algorithms in Rakai, Uganda

Abstract: Rapid HIV tests are a crucial component of HIV diagnosis in resource limited settings. In Uganda, the Ministry of Health allows for both serial and parallel HIV rapid testing using Determine, Stat-Pak and Uni-Gold. In serial testing, a non-reactive result on Determine ends testing. The performance of serial and parallel algorithms with Determine and Stat-Pak test kits was assessed. A cross-sectional diagnostic test accuracy evaluation using three rapid HIV test kits as per the recommended parallel test algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 11 publications
1
72
0
Order By: Relevance
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported using a suboptimal testing strategy that differed from the WHO recommendations [5,8,1114,16,2230,3234,36–39,4244,49,51,53,59,62,64–66,68,72,75]. Suboptimal testing strategies included using a highly specific first-line test and highly sensitive second-line test [14,33,39,55], using a single RDT for HIV-positive diagnoses [11,66,72], using a high prevalence testing strategy in a low prevalence setting [16,49], using a parallel testing algorithms and a tiebreaker testing strategy (where a third assay is used to resolve discrepant test results and rule in HIV infection) [5,12,13,16,24,25,2730,32,34,36,37,68].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of laboratory-based comparisons of RDT test kit performance have demonstrated lower than expected sensitivities with both Determine and UniGold test kits in certain settings. Gawalingo et al reported a sensitivity of 97.3% for a serial algorithm which used Determine as the screening test [27]. Kosack et al demonstrated a sensitivity of 96.2% for UniGold in a head-to-head comparison of eight RDT kits in the laboratory [28].…”
Section: Discussionmentioning
confidence: 99%